Програмна система для профілактики розвитку хвороби Альцгеймера з використанням шоломів віртуальної реальності - Шемрікович, А. Д. (ХНУРЕ, 2022)
The topic of prevention and detection of Alzheimer's disease using virtual reality technologies is currently actively developing in the scientific community. Experiments are being conducted; companies are working on prototypes. Experiments show a positive effect on the health of patients and slowing down the course of the disease since a person strains his brain. In addition, the virtual reality kit is convenient and mobile to use and can simulate the usual routine of a person that he can perform while sitting in a room.
Keywords: програмна система; віртуальна реальність